استجابة بعض الصفات الفسيولوجية لمحصول الفول (Vicia faba L.) للتسميد البوتاسي وموعد التطويش (c) - عبد العزيز محمد (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث لدراسة تأثير أربعة معدلات من السماد البوتاسي. (0، 20، 40، 60 كغ/ K2O/هـ)، وثلاثة مواعيد للتطويش (شاهد بدون تطويش، تطويش عند إزهار 50% من النباتات، تطويش عند تشكل 50% من القرون)، في بعض المؤشرات الفسيولوجية لنبات الفول، طبق تصميم القطاعات العشوائية المنشقة لمرة واحدة بثلاثة مكررات. شغلت الأسمدة البوتاسية القطع الرئيسة، وشغلت مواعيد التطويش القطع المنشقة. أظهرت الدراسة إن إضافة معدلات بوتاسية من 20 ـ 60 كغ K2O/هـ سبب زيادة معنوية في جميع الصفات المدروسة ووصلت الزيادة عند المعدل 60 كغ K2O/هـ إلى 20.95% في دليل المساحة الورقية، و71.58% في المادة الجافة، و50.30% في الغلة من القرون الجافة، و51.34% في الغلة من البذور الجافة، و39.21% في دليل الحصاد، و57.04% في دليل المحصول، و7.58% في دليل البذور بالمقارنة مع الشاهد. تفوق التطويش عند 50% إزهار، و50% تشكل قرون على الشاهد بدون تطويش في جميع الصفات المذكورة أعلاه باستثناء دليل البذور الذي لم تكن الفروق معنوية فيه بين موعدي التطويش. وسبب التطويش عند تشكل 50% من القرون زيادة معنوية في جميع المؤشرات الفسيولوجية المذكورة، وقدرت الزيادة بالمقارنة مع الشاهد بنحو 6.71%، 13.54%، 21.99%، 37.58%، 19.66%، 18.97%، 4.4% على التوالي. أعطى التداخل بين المعدلات البوتايسة وموعد التطويش تأثيراً معنوياً في جميع الصفات المذكورة، وحقق المعدل 60 كغ K2O/هـ، والتطويش عند تشكل 50% من القرون أفضل النتائج، ووصلت الزيادة في دليل البذور 6.22%. The research was carried out to study the effect of 4 rates of potassium fertilizer, (0, 20, 40, and 60 kg K2O/ha1) and 3 times of plant topping, (control, topping at 50% flowering, and topping at 50% podding) on some Physiological Traits. A split- plot arrangement with a randomized complete black design of 3 replications was used. Results showed that the application of potassium fertilizer from 20 to 60 kg K2O/ha1 significantly increased all Physiological Traits. The application of 60 kg K2O/ha1 gave significant effects. The increase reached to in 20.95% leaf area index, 71.58% in dry matter, 50.30% in dry pods, 51.34% in dry seeds, 39.21% in harvest index, 57.04% in yield index, and 7.58% in seed index in comparison to the control. Topping plants at 50% flowering and 50% podding significantly increased all studied parameters as compared to the control, except the seed index. Toping plants at 50% podding caused significant effects in all the above-mentioned Physiological Traits compared to the control, while the increase reached to 6.71%, 13.54%, 21.99%, 37.58%, 19.66%, 18.97% and 4.4% constantly in the physiological traits. There were no significant differences between the two times of topping. The interaction between rates of potassium and times of topping gave better results at rate 60 kg K2O/ha1 and potting time after 50% podding which increased seed index to 6.22%.